Utilization potentials of eucalyptus grandis (hill ex maiden) a municipal tree on the University of Ibadan campus (2009)
Selected physical and mechanical properties of 28 years old Eucalyptus grandis planted as municipal trees were evaluated to determine its utilization potentials. Five trees were selected and felled. Test samples were then taken at four different levels along the bole. The properties of the wood evaluated were moisture contents, calorific energy, impact and static bending properties. Data collected were statistically analysed using ANOVA. Statistical analysis of the results showed significant variation in the calorific energy properties, impact and static bending (MOR and MOE) along the bole of Eucalyptus grandis. Moisture content however, showed a level of axial uniformity All the results of the test carried out showed that Eucalyptus grandis is a very strong wood species, which can be used for load bearing work in construction such as flooring and paneling. Due to the high calorific energy values recorded in the study off cuts of this wood have great potentials for fuel wood and charcoal production.